Development of a metal matrix composite layer on a microalloyed steel surface by dissociating MAX211 Ti2AlC particles using a TIG torch technique. Issue 4 (2nd October 2017) - Muñoz de Escalona, P.; Lees, C.; Sillars, F.; Mridha, S.; Baker, T. N.
Abstract: A surface engineering method utilised a tungsten inert gas torch to melt a preplaced MAX211, Ti2 AlC powder particles into a microalloyed steel substrate with the aim of producing a surface metal matrix composite.. In this study, the two different shielding gases, argon and a mixture of argon + helium (80 + 20%), were used to protect the surfaces under different processing conditions, with the aim of finding the optimal conditions for further studies. An analysis of the morphology, microstructure and hardness profile of the melted zone, showed that in general, samples melted under argon achieved a higher hardness and exhibited a smaller penetration into the substrate compared to melting under a mixture of argon + helium. An XRD study showed that the Ti2 AlC powder decomposed to TiC particles dispersed in mainly TiAl.